Zebrafish-As an integrative model for twenty-first century toxicity testing - Sipes, Nisha S.; Padilla, Stephanie; Knudsen, Thomas B. (Birth defects research. Part C. Embryo today, 2011)
The zebrafish embryo is a useful small model for investigating vertebrate development because of its transparency, low cost, transgenic and morpholino capabilities, conservation of cell signaling, and concordance with mammalian developmental phenotypes. From these advantages, the zebrafish embryo has been considered as an alternative model for traditional in vivo developmental toxicity screening. The use of this organism in conjunction with traditional in vivo developmental toxicity testing has the potential to reduce cost and increase throughput of testing the chemical universe, prioritize chemicals for targeted toxicity testing, generate predictive models of developmental toxicants, and elucidate mechanisms and adverse outcome pathways for abnormal development. This review gives an overview of the zebrafish embryo for pre dictive toxicology and 21st century toxicity testing. Developmental eye defects were selected as an example to evaluate data from the U.S. Environmental Protection Agency's ToxCast program comparing responses in zebrafish embryos with those from pregnant rats and rabbits for a subset of 24 environmental chemicals across >600 in vitro assay targets. Cross‐species comparisons implied a common basis for biological pathways associated with neuronal defects, extracellular matrix remodeling, and mitotic arrest. Birth Defects Research (Part C) 93:256–267, 2011. © 2011 Wiley‐Liss, Inc.